Penerapan Finite State Machine pada Squid Game Berbasis Dekstop Menggunakan Unity 3D - Bayu, Muhamad B Kresna (JATIKOM: Jurnal Aplikasi dan Teori Ilmu Komputer, 2024)
Abstract— The emergence of modern games has resulted in children tending to play gadgets and leave traditional games. This study aims to develop a traditional 3D themed game that adapts the desktop-based Squid Game series. Squid Game 3D will be developed by applying the Finite State Machine (FSM) control system design method. In designing the game, the researchers used the Multimedia Document Life Cycle (MDLC) development method which consisted of the concept, design, material collection, assembly, and testing. The concept adapts the Red Light Green Light game found in the Squid Game film. Game designed using UML, Storyboard, and FSM. Materials needed in include writing titles, pictures of characters and images as game backgrounds. Furthermore, the game is made by coding and creating an interface using Unity 3D, Visual Studio Code, and 3D Viewer. As a result, a desktop-based 3D Squid Game was successfully developed next tested using the black box testing. and the result was that all system functions in Squid Game 3D were successfully run.